Serum lysyl oxidase concentration increases in long-standing systemic sclerosis: Can lysyl oxidase change over time? - Mohammad Hassan Jokar; Simin Jafaripour; Nafiseh Abdollahi; Maryam Nazemipour; Maliheh Moradzadeh; Mohammad Ali Mansournia (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the association of serum lysyl oxidase (LOX) levels with systemic sclerosis (SSc), to examine the relationship between LOX and disease onset, and to evaluate the probable effects of hyperlipidemia on the circulating levels of LOX among patients with SSc. Patients and methods: Between May 2017 and November 2018, a total of 39 patients with SSc (2 males, 37 females; mean age: 46.6±12.3 years; range, 18 to 65 years) and 35 healthy controls (4 males, 31 females; mean age: 43.1±14.1 years; range, 18 to 65 years) were included. Serum LOX concentration was measured using the enzyme-linked immunoassay in triplicate. Results: We found higher levels of serum LOX in patients with SSc compared to healthy controls. There was a significant relationship between serum LOX levels and disease onset. Patients with long-standing disease demonstrated increased levels of LOX in the blood compared to the recent-onset group. Hyperlipidemia did not have a significant effect on circulating levels of LOX. There was a significant negative correlation between LOX levels and modified Rodnan Skin Score in the subgroup of patients with skin involvement only and in patients without gastrointestinal involvement. Conclusion: Our study findings show an increased level of LOX protein level in the blood of patients diagnosed with SSc. Hyperlipidemia seems not to affect the concentrations of LOX in the peripheral blood of patients with SSc.